Investigation into the role of MNDA in the type 1 1FN response in human monocytes - Casserly, David (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
Type I interferons (IFNs) are secreted by cells in response to pattern recognition receptor (PRR) stimulation by viral nucleic acids and have a broad range of antiviral effects. The human PYHIN proteins, namely AIM2, IFI16, PYFIINl, POP3 and MNDA, have been established as key players in the innate immune response. AIM2 and IFI16 function as intracellular sensors of pathogen DNA, leading to inflammasome activation and production of type I IFN via the STING-TBK1-IRF3 signalling axis, respectively. Recently, PYHINl has been implicated as a DNA sensor for herpesvirus DNA and POP3 was shown to be a negative regulator of PYFIIN inflammasome responses. The aim of this project was to determine if the fifth human PYFIIN, MNDA, had any function in PRR responses
Keywords: Biochemistry & Immunology, Ph.D.; PhD Trinity College Dublin, 2015